'Feedback interpreters': the role of learning development professionals in facilitating university students' engagement with feedback. Issue 6 (18th August 2019) - Gravett, Karen; Winstone, Naomi E.
ABSTRACT: Understanding how students engage with assessment feedback is a key concern of higher education professionals. Research commonly represents the perspectives of students and academic staff, yet little consideration is given to the role of learning development staff, despite these individuals supporting students when interpreting and implementing feedback. We report the findings from interviews with learning developers working in a UK University, exploring their insights into the barriers students confront when engaging with feedback, and into the role of learning developers within the feedback landscape. This study suggests that, while many challenges exist for staff and students in the context of assessment feedback, learning development professionals are able to provide a meaningful source of guidance, in partnership with academic staff, and are able to promote students' development through dialogic interactions. Hitherto these interactions have not been fully explored, yet they provide powerful insight into the hidden processes of feedback recipience.